Grafting influences phenolic profile and carpometric traits of fruits of greenhouse-grown eggplant (Solanum melongena L.) - Kacjan Maršić, Nina; Mikulič-Petkovšek, Maja; Stampar, Franci (Journal of agricultural and food chemistry, 2014)
The influence of eggplant grafting on tomato rootstock was evaluated during the two growing seasons. Yield, quality traits, and individual phenolics in fruits were assessed. Three commercial varieties and one landrace were used as scions. Grafting significantly increased eggplant yield and decreased the presence of calyx prickles. The effect of grafting on the accumulation of major phenolic constituents in eggplant fruit was inconsistent: in the year with less solar radiation and lower mean daily air temperatures, grafting decreased phenolic content in commercial variety/rootstock fruit and increased the content in landrace/rootstock fruit. An opposite effect in the latter combination was observed in the year with improved conditions for eggplant cultivation. The browning potential of fruit pulp was highly dependent on variety/landrace and partly also on grafting combination. Differences in correlations between phenolic constituents and browning potential (positive for varieties and negative for landrace) could also be ascribed to the importance of other antioxidants for diminished eggplant pulp browning.